Outcomes of Peginterferon Alpha-2a and Ribavirin Hepatitis C therapy in Aboriginal Canadians - Curtis L Cooper; Robert J Bailey; Vince G Bain; Frank Anderson; Eric M Yoshida; Mel Krajden; Paul Marotta; for the Canadian Pegasys Study Group (Canadian Journal of Gastroenterology)
BACKGROUND: There is little published information on baseline characteristics and therapeutic outcomes in hepatitis C virus (HCV)-infected Aboriginal Canadians. It is unclear what proportion of HCV-infected Aboriginal people receive therapy relative to other populations.